BUSINESS ANALYSIS OF PATIN FISH CULTIVATION (Pangasius sutchi) IN POLY WITH SYSTEM FOR RESULTS IN KUOK VILLAGE DISTRICT KAMPAR RIAU PROVINCE - Kurniawan, Obi; Yulinda, Eni; Kusai, Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT                Research on Analysis of Patin Fish Farming Business (Pangasius sutchi) in this pond was conducted in January 2018 in Kuok Village, Kampar regency, Riau Province. This study aims to (1) find out how big the total investment from Patin Fish Farming (Pangasius sutchi) in pond, (2) to know the level of profit from Patina Fish Cultivation (Pangasius sutchi) in Pond, (3) to know the problem faced by Patina Fish (Pangasius sutchi) in ponds, (4) knowing the things that cause the Cultivators of Patin Fish (Pangasius sutchi) to share the system. The method used is survey method which includes observation, interview and documentation.               Based on the result of the research, (1) the total investment from Pasta Fish (Pangasius sutchi) in the Pond with the Profit Sharing System is IDR.3.298.598.700, (2) while the total net profit / income obtained by the Patin Fishers in the Pond is between IDR. 19.007.850, up to IDR.54.174.250, (3) the problems faced by the cultivators is in the form of a very large business capital in conducting Patin Fish Farming (Pangasius sutchi) in Pond, (4) Patin Fish Farming in Pond is feasible to done with RCR value> 1, with value of ROI between 8,65% -23,81%, and value of PPC 7,60-11,56 / period. Keywords: Patin Fish Cultivation in Pond, Business Analysis, Kuok Village.